2010
DOI: 10.3109/00365521.2010.545832
|View full text |Cite
|
Sign up to set email alerts
|

“Pelvic radiation disease”: New understanding and new solutions for a new disease in the era of cancer survivorship

Abstract: Radiation-induced gastrointestinal toxicity is bedeviled by inappropriate terminology, causing confusion, and myth which legitimizes inappropriate clinical behavior. We must address honestly the uncomfortable reality that doctors, sometimes do harm. Not to do so in an era where survivorship is a reality, will deny millions often with severe symptoms from "pelvic radiation disease", the care which will help them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 63 publications
1
69
0
3
Order By: Relevance
“…Radiotherapy of malignancies in the pelvic region is frequently used. Still, as Andreyev and coworkers [1] emphasise, the knowledge of pelvic radiation disease is limited. The authors give a very thorough review of our knowledge about this disease, stating that "radiation-induced gastrointestinal toxicity is bedeviled by inappropriate terminology, causing confusion and myth which legitimizes inappropriate clinical behaviour"!…”
Section: This Month In Scandinavian Journal Of Gastroenterologymentioning
confidence: 97%
“…Radiotherapy of malignancies in the pelvic region is frequently used. Still, as Andreyev and coworkers [1] emphasise, the knowledge of pelvic radiation disease is limited. The authors give a very thorough review of our knowledge about this disease, stating that "radiation-induced gastrointestinal toxicity is bedeviled by inappropriate terminology, causing confusion and myth which legitimizes inappropriate clinical behaviour"!…”
Section: This Month In Scandinavian Journal Of Gastroenterologymentioning
confidence: 97%
“…However, these consequences of radiotherapy are now recognized as pelvic radiation disease (PRD) (11,12). As with all diseases, PRD can be transient or chronic, can be understood anatomically (it affects noncancerous tissues exposed to radiotherapy given for a pelvic tumor), has defined symptoms (13) (which can vary from mild to very severe), has a typical pathophysiology (14,15) and can be easily identified using responses to simple questions (16).…”
Section: Pelvic Radiation Disease: a Consequence Of The Survivorship Eramentioning
confidence: 99%
“…Rectal bleeding occurs in up to 50% of patients who previously received pelvic radiotherapy,39–42 but requires therapeutic intervention in fewer than 6%13 16 with 1–5% becoming transfusion dependent 9. Rectal bleeding typically starts about 1 year after conformal radiotherapy for prostate cancer and is at its worst at 3 years before improving spontaneously over 5–10 years 37.…”
Section: An Approach To Rectal Bleedingmentioning
confidence: 99%
“…Therefore, in these complex patients, a systematic, algorithmic approach to assess and treat the symptoms effectively is required 7 13. Just such an approach has recently been tested in a large randomised NIHR funded clinical trial, the ORBIT study (ISCRCTN 22890916) and shown to produce significant benefit (unpublished data).…”
Section: Introductionmentioning
confidence: 99%